The Relationship of Markers With Carotid Artery Stenosis and Lesion Hardness: Superiority of C-Reactive Protein and Uric Acid - Alp Yildirim; Mustafa Celik; Muhammed Fatih Kaleli; Fikret Keles; Muhammed Alpaslan; Erdogan Sokmen (Avicenna Journal of Medical Biochemistry, 2023)
Background : Atherosclerosis is a disease that cholesterol plaque builds up inside arteries. The process of atherosclerosis starts when certain substances such as cholesterol, fats, and cellular waste products accumulate in the walls of arteries, and the immune system responds to these substances, triggering inflammation. Over time, this inflammation can cause the plaque to grow and harden, narrowing the artery and reducing blood flow. Carotid artery disease (CAD) is a conclusion of plaques in carotid artery. CAD can increase the risk of stroke, a potentially life-threatening condition that occurs when blood flow to the brain is interrupted. Objectives: The objectives of this study were to detect the association between carotid artery stenosis and inflammatory markers. Methods: This study was designed prospectively and included 109 and 100 patients having mild carotid stenosis and severe carotid stenosis, respectively. Further, 101 patients were included in the control group. The carotid ultrasonography was evaluated in all patients. After classifying the plaques into<60% (mild stenosis) and 60%>(severe stenosis) categories, they were also grouped into echogenicity plaques, namely, echolucent (soft) and echogenic (hard) plaques. Results: The uric acid (UA) values of the mild and severe stenosis groups were higher than that of the control group (P<0.01). The mean C-reactive protein (CRP) value was the highest in the severe stenosis group, and the lowest CRP value was found in the control group (P<0.01). A one-unit increase in UA could increase the risk by 2.203 times. The CRP value was higher in the soft lesion group without calcification than in the hard lesion group with calcification. Conclusion: Our findings demonstrated that age, UA, and CRP values were identified as predictors independent of each other in the development of carotid stenosis. Regarding plaque classification, our results identified CRP, mean platelet volume (MPV), white blood cell, and lymphocyte values as negative predictors. The findings of our study indicate that CRP and UA are valuable in predicting the severity of stenosis and the formation of soft plaque.